Hydrodynamic tests on a plate in forced oscillation - Klaka, Kim; Penrose, John; Horsley, Richard; Renilson, M. (Elsevier, 2006)
AbstractThe forces and moments acting on an oscillating plate at inflow angles at or below stall are well understood. However, there is ashortage of data on surface-piercing plates undergoing rotational oscillation. A set of experiments was conducted on a series of flat platesundergoing forced rotational oscillation in calm water. The impetus for the experiments was an investigation into the hydrodynamics ofsailing yacht keels, but the results may be of value for a wide range of engineering problems. The experiments showed that the twodimensionalcase was not representative of three-dimensional flow conditions. There was a possible region of transitional flow for theplate in two-dimensional flow, not evidenced in the results for three-dimensional flow. The total roll moment, roll inertia, roll drag andsway force coefficients showed an inverse square root relationship to aspect ratio, with a very weak dependency on oscillation frequencyand angle amplitude. Under-plate clearance effects were small for the clearance values investigated.r 2006 Elsevier Ltd. All rights reserved.